AN ANALYSIS OF PAUSES, OVERLAPS AND BACKCHANNELS IN CONVERSATION IN VLOG BY NESSIE JUDGE - Kuswandi, Meydiana; Apsari, Yanuarti (IKIP Siliwangi, 2019)
This research focuses on pauses, overlaps, and backchannels based on conversation in vlog of Nessie Judge with title tips in speaking English. The duration the vlog is 7:32 minutes posted on November 27, 2016 on Nessie’s youtube account. When the speaker is speaking will occur in the conversation, become a reason the resercher to anlyze pauses, overlaps, and backchannels. The purpose of this research is to find out what the types of pauses, overlaps, and backchannels and how the pauses, overlaps, and backchannels in the conversation between Nessie and her partner. This research used qualitative method. To collect the data the researcher watched the vlog of Nessie. After the data collected, the data was classified into types of pauses, overlaps, and backchannels. Then, the reasercher analyzed the reason behind of it. The result of this research showed that there are two types of pauses in conversations. Filler and unfiller pause. And also there are two types of backchannels. Vocal backchannel and non vocal backchannel. And the last is overlaps which only once during the duration of the vlog.Keywords: conversation analysis, pauses, overlaps, backchannels, vlog